The Pan-African Parliament’s Unfinished Legislative Mandate and the Sovereignty Challenge of Its Continental Legislative Diplomacy - Zhizhi Meshach Rizama; Abah Innocent; Zhizhi Emmanuel Jiruma (Universitas Muhammadiyah Makassar, 2026)
This study examines how the Pan-African Parliament (PAP) exercises legislative diplomacy without formal legislative authority, why African Union member states withhold ratification of the 2014 Malabo Protocol, and what this reveals about sovereignty and regional integration. Employing a qualitative case study design, the research analyzes 67 documents including official AU and PAP records, member state communications, and academic literature spanning 2004 to 2025. Through thematic analysis and qualitative content analysis using deductive and inductive coding, the study identifies three key findings. First, the PAP has developed a modality of